2018
DOI: 10.3762/bjnano.9.165
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of micro/nanopatterned gelatins crosslinked with genipin for biocompatible dental implants

Abstract: Background: Collagen is a basic component of the periodontium and plays an important role in the function of the periodontal unit. Therefore, coating with collagen/gelatin has been applied to enable dental implants to positively interact with peri-implant tissues. Although the micro/nanoscale topography is an important property of the surface of dental implants, smaller collagen/gelatin surface patterns have not been sufficiently developed. Furthermore, only few reports on the behavior of cells on gelatin surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…112 Micromolding and nanopatterning are techniques used to modify substrate surfaces to accommodate various geometric patterns and configurations that control the behavior of the cells by imposing spatial restrictions to cell attachment, spreading, etc. [113][114][115] Due to the advent of technology, surface modifications such as micromolding and nanopatterning can be achieved with various techniques such as Owing to its biocompatibility and biodegradability, gelatin has been widely used in both 2D (surface coatings, microsheets) and 3D (hydrogels, microparticles) biomaterial platforms for the enhanced proliferation and assisted differentiation of several types of cells and tissues in vitro.…”
Section: Gelatin-based 2d Biomaterials For Cell and Tissue Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…112 Micromolding and nanopatterning are techniques used to modify substrate surfaces to accommodate various geometric patterns and configurations that control the behavior of the cells by imposing spatial restrictions to cell attachment, spreading, etc. [113][114][115] Due to the advent of technology, surface modifications such as micromolding and nanopatterning can be achieved with various techniques such as Owing to its biocompatibility and biodegradability, gelatin has been widely used in both 2D (surface coatings, microsheets) and 3D (hydrogels, microparticles) biomaterial platforms for the enhanced proliferation and assisted differentiation of several types of cells and tissues in vitro.…”
Section: Gelatin-based 2d Biomaterials For Cell and Tissue Culturesmentioning
confidence: 99%
“…Extensive reviews on the different micro and nano surface patterning techniques are available elsewhere. 113,116 Gelatin surface modifications have also been conducted for cell and tissue engineering purposes. 115,117 In one study, mmolded gelatin crosslinked with bacterial glutaminase performed better compared with 2D-coated ECM matrices in maintaining cultures of skeletal myotubes in vitro for 3 weeks.…”
Section: Gelatin Biomaterials: From Cell Culture To Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[55] Previously, genipin concentrations ranging from 0.02 to 100 mm have been used for cross-linking. [38,[40][41][42][43]45,46,[48][49][50][52][53][54]56,57,[65][66][67][68][69] However, some studies have shown that genipin concentrations of 5 mm and above have cytotoxic effects. [41,51,67] In one study, 1 mm genipin cross-linked samples promoted proliferation and viability of an neural stem cell line (SPC-01) and outgrowth of dissociated adult dorsal root ganglion neurons; these samples also displayed in vivo biocompatibility when injected into focal ischemic lesion in the rat motor cortex.…”
Section: Incorporating Genipin Into Coll/cs Slurry Prior To Freeze-drmentioning
confidence: 99%
“…Natural cross‐linkers such as genipin have demonstrated equally efficient cross‐linking, while also offering a safer alternative having been FDA approved for use as a food dye (under the name “fruit juice”) 36,37. Genipin has been successfully used for cross‐linking of other collagen‐based materials such as biological tissues,38–44 collagen films,45 gelatin,38,46–50 ECM hydrogels,51 collagen‐chitosan blends,52–55 and other natural polymers;56,57 it also possesses significant anti‐inflammatory properties 58,59. Indeed, a recent study from our group showed that genipin cross‐linking dampens both pro‐ and anti‐inflammatory responses from macrophages,60 one of the first innate immune cells to encounter an implanted biomaterial 61…”
Section: Introductionmentioning
confidence: 99%